218. Changes in Dental Antibiotic Prescribing in the United States, 2012–2017. (31st December 2020) - Ramanathan, Swetha; Yan, Connie H; Hubbard, Colin; Calip, Gregory; Sharp, Lisa K; Rowan, Susan A; McGregor, Jessina C; Gross, Alan E; Campbell, Allen; Evans, Charlesnika T; Hershow, Ronald; Suda, Katie J
Abstract: Background: Data suggest dental antibiotic prescribing is increasing with relatively less documented about prescribing trends in adults and children. Therefore, the aim was to evaluate trends in antibiotic prescribing by US dentists from 2012–2017. Methods: This was a cross-sectional study of US dental prescribing using IQVIA Longitudinal Prescription Data from 2012 to 2017. Prescribing rates (prescriptions [Rx] per 100, 000 dentists), mean days' supply, and mean quantity dispensed were calculated monthly across eight oral antibiotic groups: amoxicillin, clindamycin, cephalexin, azithromycin, penicillin, doxycycline, fluoroquinolone, and other antibiotics. Descriptive frequencies and multiple linear regressions were performed to obtain trends overall and stratified by adults (≥ 18) and children (< 18). Results: 220, 325 dentists prescribed 135 million Rx (94.0% in adults). 61.0% were amoxicillin, 14.4% clindamycin, 11.7% penicillin, 4.4% azithromycin, 4.3% cephalexin, 2.0% other antibiotics, 1.4% doxycycline, and 0.7% fluoroquinolones. Prescribing increased by 33 Rx/100, 000 dentists (p< 0.0001) each month for all antibiotics. Amoxicillin (p< 0.0001) and clindamycin (p=0.02) prescribing rate increased by 73 and 5 Rx/100, 000 dentists, respectively. Prescribing decreased by 8, 12, and 2 Rx/100, 000 dentists for cephalexin (p< 0.0001), doxycycline (p< 0.0001), and fluoroquinolones (p=0.008), respectively. Mean days' supply increased for amoxicillin, penicillin, and clindamycin (p< 0.0001), and decreased for cephalexin (p< 0.0001).Mean quantity dispensed decreased (p< 0.0001) for all groups except azithromycin and doxycycline. Among adults, cephalexin prescribing rates (7 Rx/100, 000 dentist; p< 0.0001) and other antibiotics days' supply (p< 0.0001) decreased. Among children, azithromycin prescribing rates (1 Rx/100, 000 dentists, p=0.02), and fluoroquinolone and other antibiotics days' supply (p< 0.0001) decreased. Conclusion: These findings support dental antibiotic prescribing is increasing, specifically for amoxicillin and clindamycin. Further, trends differed between adults and children. Understanding what is driving these trends is important to target dental antibiotic stewardship efforts. Disclosures: All Authors : No reported disclosures